The Effect of Firm-Specific Risk and Macro Economic Factors on The Performance of Islamic and Conventional Bank - Annisa Suriyati; Marwansyah Marwansyah; Mochamad Edman Syarif (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The performance of Islamic banks still fluctuates every year and even their performance ratios are still below the BI standard per bank. The purpose of this research is to evaluate the impact of firm-specific risk (credit risk, liquidity risk and operational risk) and macroeconomic factors (inflation, GDPG and unemployment) on the performance of Islamic commercial banks and conventional banks (ROA) in Indonesia. Comparison of Islamic banks with conventional banks is made because of differences in the respective banking operations/systems. The research uses quantitative research methods with secondary data on Islamic and conventional banking recorded at BI and OJK for the 2017-2021 period. The result in Islamic banks, only the credit risk variable and operational risk II variable have a significant negative effect on the ROA of Islamic banks. The other four variables have no effect on the performance of Islamic banks. In conventional banks, operational risk II variables, inflation and GDP have a significant effect on conventional bank ROA. The other three variables have no effect on the performance of conventional banks.